2009
DOI: 10.1200/jco.2008.21.2712
|View full text |Cite
|
Sign up to set email alerts
|

Professionals Assess the Acceptability of Preimplantation Genetic Diagnosis and Prenatal Diagnosis for Managing Inherited Predisposition to Cancer

Abstract: With the most severe forms of inherited cancer, no differences were observed between the acceptability to practitioners of PND and PGD, but with late-onset syndromes, there is still much uncertainty. Guidelines would help to standardize the practices of professionals handling these reproductive issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 11 publications
1
39
1
Order By: Relevance
“…15 Earlier versions of the HFEA Code of Practice (sixth edition, 2003) stated: 'Indications for the use of PGD are expected to be consistent with current practice in the use of (post-implantation) prenatal diagnosis (PND)' . 16 This ethical premise is supported by findings among health professionals in France 17 that there is no difference in acceptability of one procedure compared with the other with respect to cancer predisposition. The clause was removed from later editions of the Code of Practice.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…15 Earlier versions of the HFEA Code of Practice (sixth edition, 2003) stated: 'Indications for the use of PGD are expected to be consistent with current practice in the use of (post-implantation) prenatal diagnosis (PND)' . 16 This ethical premise is supported by findings among health professionals in France 17 that there is no difference in acceptability of one procedure compared with the other with respect to cancer predisposition. The clause was removed from later editions of the Code of Practice.…”
Section: Introductionsupporting
confidence: 57%
“…In France 17 and Spain, 32 approximately half of health professionals surveyed are of the opinion that PND/PGD should be offered for BRCA. In the United States, approximately half of gynaecological oncologists and obstetric/gynaecologists surveyed thought PGD appropriate for BRCA; o20% reported that they were 'knowledgeable' or 'very knowledgeable' about PGD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As parents are now routinely discussing these options in planning future pregnancies, the need to engage a multidisciplinary team in these discussions is key to providing parents and families with the necessary tools to make these ethically challenging decisions. 84,92,93 While some studies suggest the benefits to predictive genetic testing for children are still not substantial, further evaluations from different perspectives will continue to evolve this field. 93,95 Several recommendations established in 1992 for LFS 96 are still applicable to genetic testing in family cancer syndromes that include children.…”
Section: Medical and Ethical Considerationsmentioning
confidence: 99%
“…The quality of information provision on cancer genetics is directly related to the knowledge of professionals and their ability to communicate this to a patient and family, regardless of their specialty. 96 The multidisciplinary approach taken by several groups 92,97 involving pediatric and medical oncologists, clinical geneticists, genetic counselors, psychologists, and ethicists in establishing cancer genetics clinics and programs provides a novel mechanism that should be considered standard to optimize care of these families and advance our understanding of the role of genetics in the etiology and management of LFS.…”
Section: Medical and Ethical Considerationsmentioning
confidence: 99%